Poplar MYB115 and MYB134 Transcription Factors Regulate Proanthocyanidin Synthesis and Structure. Issue 1 (27th March 2017) - James, Amy Midori; Ma, Dawei; Mellway, Robin; Gesell, Andreas; Yoshida, Kazuko; Walker, Vincent; Tran, Lan; Stewart, Don; Reichelt, Michael; Suvanto, Jussi; Salminen, Juha-Pekka; Gershenzon, Jonathan; et al.
Abstract : Two MYB transcription factors form the core of a gene regulatory network that controls the accumulation and hydroxylation pattern of proanthocyanidins in poplar. Abstract: The accumulation of proanthocyanidins is regulated by a complex of transcription factors composed of R2R3 MYB, basic helix-loop-helix, and WD40 proteins that activate the promoters of biosynthetic genes. In poplar (genus Populus ), MYB134 is known to regulate proanthocyanidin biosynthesis by activating key flavonoid genes. Here, we characterize a second MYB regulator of proanthocyanidins, MYB115. Transgenic poplar overexpressing MYB115 showed a high-proanthocyanidin phenotype and reduced salicinoid accumulation, similar to the effects of MYB134 overexpression. Transcriptomic analysis of MYB115- and MYB134-overexpressing poplar plants identified a set of common up-regulated genes encoding proanthocyanidin biosynthetic enzymes and several novel uncharacterized MYB transcriptional repressors. Transient expression experiments demonstrated the capacity of both MYB134 and MYB115 to activate flavonoid promoters, but only in the presence of a basic helix-loop-helix cofactor. Yeast two-hybrid experiments confirmed the direct interaction of these transcription factors. The unexpected identification of dihydromyricetin in leaf extracts of both MYB115- and MYB134-overexpressing poplar led to the discovery of enhanced flavonoid B-ring hydroxylation and an increased proportion of prodelphinidins in proanthocyanidin of the transgenics. The dramatic hydroxylation phenotype of MYB115 overexpressors is likely due to the up-regulation of both flavonoid 3′, 5′-hydroxylases and cytochrome b 5 . Overall, this work provides new insight into the complexity of the gene regulatory network for proanthocyanidin synthesis in poplar.